Altered stability of etoposide-induced topoisomerase II-DNA complexes in resistant human leukaemia K562 cells. - Ritke, M. K. (Nature Publishing Group, 1994)
K562 leukaemia cells were selected for resistance using 0.5 microM etoposide (VP-16). Cloned K/VP.5 cells were 30-fold resistant to growth inhibition by VP-16 and 5- to 13-fold resistant to m-AMSA, adriamycin and mitoxantrone. K/VP.5 cells did not overexpress P-glycoprotein; VP-16 accumulation was similar to that in K562 cells. VP-16-induced DNA damage was reduced in cells and nuclei from K/VP.5 cells compared with K562 cells. Topoisomerase II protein was reduced 3- to 7-fold and topoisomerase II alpha and topoisomerase II beta mRNAs were each reduced 3-fold in resistant cells. After drug removal, VP-16-induced DNA damage disappeared 1.7 times more rapidly and VP-16-induced DNA-topoisomerase II adducts dissociated 1.5 times more rapidly in K/VP.5 cells than in K562 cells. ATP (1 mM) was more effective in enhancing VP-16-induced DNA damage in nuclei isolated from sensitive cells than in nuclei from resistant cells. In addition, ATP (0.3-5 mM) stimulated VP-16-induced DNA-topoisomerase II adducts to a greater extent in K562 nuclei than in K/VP.5 nuclei. Taken together, these results indicate that resistance to VP-16 in a K562 subline is associated with a quantitative reduction in topoisomerase II protein and, in addition, a distinct qualitative alteration in topoisomerase II affecting the stability of drug-induced DNA-topoisomerase II complexes. IMAGES: